2012
DOI: 10.1155/2012/202906
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Array Pattern Synthesis Using a Hybrid WARP/2LB-MOPSO Algorithm

Abstract: This paper addresses conformal array synthesis as a constrained multiobjective optimization problem. Simultaneous reduction of side lobe level (SLL) and cross-polarization (XPL) level is aimed with a constraint on main beam direction. A hybrid of weighted alternating reverse projection (WARP) and two local best multiobjective particle swarm optimization (2LB-MOPSO) is proposed to optimize the pattern. First, the WARP method finds a moderate and feasible solution. Second, 2LB-MOPSO begins with an initial popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…These advantages include a broad beamwidth, wide angular coverage, full integration to the curved surface, space conservation, and reduction in the hydrodynamic dragging effect [ 1 , 2 , 3 ]. Conformal volumetric arrays on a doubly curved surface similar to a spherical array (SA) are regarded as the most effective geometric configuration for applications requiring a hemispherical beam coverage [ 4 , 5 ]. Consequently, the design of an SA has been a subject of interest to many researchers for decades and numerous studies related to that have been reported in the literature [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These advantages include a broad beamwidth, wide angular coverage, full integration to the curved surface, space conservation, and reduction in the hydrodynamic dragging effect [ 1 , 2 , 3 ]. Conformal volumetric arrays on a doubly curved surface similar to a spherical array (SA) are regarded as the most effective geometric configuration for applications requiring a hemispherical beam coverage [ 4 , 5 ]. Consequently, the design of an SA has been a subject of interest to many researchers for decades and numerous studies related to that have been reported in the literature [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%